1999
DOI: 10.1093/jat/23.7.581
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonium Salts as Derivatizing Agents. 3. Quantitation of the Cocaine Metabolite Benzoylecgonine in Urine Using Gas Chromatography with Ion-Pair Extraction/On-Column Alkylation*

Abstract: Recent studies have demonstrated the utility of quantitative assays for benzoylecgonine in assessing the efficacy of cocaine-dependence-treatment programs to determine if the amount of cocaine consumed has been reduced. We describe a simple gas chromatographic method for determining benzoylecgonine concentrations in urine. BZE is extracted from urine as an ion pair with tri-n-propylsulfonium ion. Injection into the heated injection port of the gas chromatograph results in thermal conversion of the ion pair to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Several methods have been reported for the identification and quantification of COC and its metabolite in urine samples. These include immunoassay [1][2][3], gas chromatography [4][5][6][7], gas chromatography-mass spectrometry (GC-MS) [2,[8][9][10][11][12][13][14][15][16][17], and time-of-flight secondary ion mass spectrometry (TOF-SIMS) [18]. Currently, immunoassays are frequently employed for the identification of cocaine and its metabolites in biological fluids but it cannot be considered as a reliable quantitative assay because normally all positive results must be confirmed by other quantitative methods.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been reported for the identification and quantification of COC and its metabolite in urine samples. These include immunoassay [1][2][3], gas chromatography [4][5][6][7], gas chromatography-mass spectrometry (GC-MS) [2,[8][9][10][11][12][13][14][15][16][17], and time-of-flight secondary ion mass spectrometry (TOF-SIMS) [18]. Currently, immunoassays are frequently employed for the identification of cocaine and its metabolites in biological fluids but it cannot be considered as a reliable quantitative assay because normally all positive results must be confirmed by other quantitative methods.…”
Section: Introductionmentioning
confidence: 99%
“…There are several analytical techniques available to determine these compounds. Chromatographic methods are the most extensively used, [1][2][3][4] because they have high sensitivity and good selectivity, but the procedures are lengthy and often involve derivatisation methods to convert the analytes to detectable forms or to improve the column efficiency and peak shapes. During recent years, some alternative, more rapid, methods have been developed for screening purposes.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few types of SPE, including reversed phase, normal phase, and ion exchange. Reverse phase and ion exchange will be discussed in the chromatography section [16]. In the most recent research, SPE has been reported to be combined with other characterization techniques (chromatography and biosensors) to improve its accuracy and selectivity.…”
Section: Solid Phase Extraction (Spe)mentioning
confidence: 99%